Iconization of Local Culture for Banyumas Community in Development - Arif, Hidayat; Fariz, Nizar; Faiqbal, Latif (Indonesian Academy of Social and Religious Research (IASRR), 2025)
This paper aims to explore the elements of local culture that have become iconic symbols of Banyumas' cultural identity in the millennial era. It examines the community's perception of development grounded in these cultural icons and analyzes the processes of iconization and socialization of local culture within Banyumas' developmental framework. The study reveals that oral traditions, historical manuscripts, customs, folk games, traditional technologies, arts, language, and rituals are central to Banyumas' cultural identity today. The society highly values the transmission of arts and culture to younger generations, emphasizing traditional dance, music, and crafts. Moreover, there is a strong sense of pride in local tourist attractions, which are vital in promoting regional culture and supporting cultural revitalization. Despite modernization, concerns persist about preserving historical buildings unique to Banyumas. The paper highlights that successful iconization and socialization involve engaging the community through education and familiarization with cultural symbols. Promoting Banyumas' cultural icons to reach millennials effectively should leverage social media, influential figures, and media collaborations to enhance awareness and support sustainable cultural development.